Answer:
The given expression at p = 5 can be written as:
![4(p^4) > 2p -3](https://img.qammunity.org/2020/formulas/mathematics/middle-school/k2o2yjsev2zhyreotht66mk1nq35w49aas.png)
Explanation:
Here, the given expressions are:
![(4p^4 ), (2p-3)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/22vzkcnb6pfreukc8l8o8zon2e6n0ewgho.png)
Now, substitute the value of p = 5 in both the given expressions, we get:
![4(p^4) = 4(5^4) = 4 (625) = 2,500\\\implies 4(p^4) = 2,500](https://img.qammunity.org/2020/formulas/mathematics/middle-school/omc32tbmfebctpzuw7l45eb7ylclplqi6d.png)
Similarly,
![(2p-3) = 2(5) - 3 = 10 -3 = 7\\\implies 2p - 3 = 7](https://img.qammunity.org/2020/formulas/mathematics/middle-school/gy32jzmdj0pqwq9hgvmrm71ttt9hw61ib9.png)
So,now comparing both the values at p = 5, we get:
2,500 > 7
![\implies 4(p^4) > 2p -3](https://img.qammunity.org/2020/formulas/mathematics/middle-school/kin10auvq8s20ebnplbqm3f0ey876q9u91.png)
Hence, the given expression at p = 5 can be written as:
![4(p^4) > 2p -3](https://img.qammunity.org/2020/formulas/mathematics/middle-school/k2o2yjsev2zhyreotht66mk1nq35w49aas.png)